Translanguaging Practices and Identity Construction of Multilingual Malaysian University Graduates in Digital Media (多語馬來西亞大學畢業生於數位媒體中的跨語際實踐與身份建構) - Ng, Lee Luan; Lee, Si Loon (Springer International Publishing, 2019)
Translanguaging has received increasing attention from linguists and scholars. Although there have been studies investigating translanguaging practices in the classroom settings, there is a lack of studies that involve multilinguals and their multiliteracy skills in digital media. In view of the popularity of digital media, such as social media, as a means of social interactions among young people in multilingual and multicultural societies, this study aims to investigate the translanguaging practices of Malaysian university graduates in digital media. The research focus is on the digital postings of a group of university graduates in social media and emails, with an aim to investigate how they utilize their linguistic repertoires such as language choice in different online dialogic exchanges. The research also aims to explore how these young adults construct their identity through their translanguaging practices within the digital media. The findings of the study show that there are four factors affecting translanguaging practices and two factors influencing identity construction through translanguaging. Among others, the findings suggest that multilingual employees perhaps should be allowed to practice translanguaging at the workplace, as it helps to facilitate specific work-related processes. Simultaneously, translanguaging practices also enable the multilinguals to maintain their sense of identity through their linguistic expressions. © 2019, National Taiwan Normal University.